Interobserver agreement and diagnostic accuracy of shearwave elastography for the staging of hepatitis C virus‐associated liver fibrosis. Issue 2 (29th August 2019) - Kaposi, Pál N.; Unger, Zsuzsanna; Fejér, Bence; Kucsa, András; Tóth, Ambrus; Folhoffer, Anikó; Szalay, Ferenc; Bérczi, Viktor
Abstract: Purpose: Our study aimed to evaluate the technical success rate, interobserver reproducibility, and accuracy of shearwave elastography (SWE) in the staging of hepatitis C virus (HCV)‐associated liver fibrosis. Methods: A total of 10 healthy controls and 49 patients with chronic liver disease were enrolled prospectively. Two examiners performed point shearwave elastography (pSWE) and two‐dimensional shearwave elastography (2D‐SWE) measurements with an RS85A ultrasound scanner using the S‐Shearwave application (Samsung Medison, Hongcheon, Korea). The performance of S‐Shearwave in the staging (METAVIR F0‐F4) of liver fibrosis was compared with prior transient elastography (TE) with receiver operating characteristic (ROC) curve analysis. Results: The interobserver reproducibility was excellent with pSWE (ICC = 0.92, 95% CI: 0.86‐0.95, P < .001). A very good agreement was found between pSWE and TE measurements (ICC =0.85, 95% CI: 0.78‐0.89, P  < .001). The ROC analysis determined the optimal cut‐off values of pSWE for the staging of chronic hepatitis C‐associated fibrosis (F2, 1.46 m/s; F3, 1.63 m/s; F4, 1.95 m/s). Both observers achieved excellent diagnostic accuracy (AUROC: 94% vs 97%) in the detection of significant (≥F2) liver fibrosis. Conclusion: The interobserver agreement is excellent with S‐Shearwave pSWE, and observers can diagnose significant liver fibrosis with a comparable accuracy to TE.